2014
DOI: 10.3329/cbmj.v3i1.53326
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Microalbuminuria with Relation to Glycemic Control in Type-2 Diabetic Patients in Mymensingh

Abstract: Diabetes is one of the most common endocrine disorders characterized by hyperglycaemia. Diabetic nephropathy is a consequence of long standing diabetes. The prevalence of microalbuminuria predicts progression to diabetic nephropathy. The present study was conducted to determine the prevalence of microalbuminuria in relation to duration of diabetes, BMI, Serum Creatinine and HbA1c in an ethnic group of Type 2 diabetes mellitus residing in Mymensingh, Bangladesh. This descriptive cross-sectional study was carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…16 The present study demonstrated that higher proportion of patient (56.7%) with microalbuminuria had poor glycemic control that is serum HbA1c > 6.5%. These findings are consistent with the other Pakistani studies by Sheikh et al and Hasan et al 17,18 These studies also reported a significant correlation of microalbuminuria with HbA1c level among type 2 diabetic patients. Moreover, Ahmed et al and Walraven et al also reported a strong correlation between the higher glycemic level and microalbuminuria.…”
Section: Discussionsupporting
confidence: 92%
“…16 The present study demonstrated that higher proportion of patient (56.7%) with microalbuminuria had poor glycemic control that is serum HbA1c > 6.5%. These findings are consistent with the other Pakistani studies by Sheikh et al and Hasan et al 17,18 These studies also reported a significant correlation of microalbuminuria with HbA1c level among type 2 diabetic patients. Moreover, Ahmed et al and Walraven et al also reported a strong correlation between the higher glycemic level and microalbuminuria.…”
Section: Discussionsupporting
confidence: 92%
“…The finding was almost similar to the study conducted by Yaffeet al 6 , 2009 and Barzilay et al10 . In this study the mean age of onset of DM was 41.6±6.9 years with minimum age 23 and maximum 54 years which is similar to the study conducted by Hasan et al11 . Study conducted by Yaffeet al6 and Akrivos et al12 showed that the mean duration of diabetes was 10.4 ± SD 7.3 years.…”
supporting
confidence: 90%
“…15 In another study in a primary care center, the prevalence of albuminuria was 17.9% among diabetes patients and 10.8% among hypertension patients. 16 Poor glycemic control has been correlated with albuminuria in various studies using HbA1C, [17][18][19][20][21] while intensive glucose control reduces the risk of albuminuria. 21 However, although studies have been conducted in different ethnic groups, few studies have included any significant proportion of Hispanic patients, despite the evidence that there are ethnic variations in albuminuria prevalence among diabetic patients.…”
Section: Introductionmentioning
confidence: 99%